2016
DOI: 10.1371/journal.pone.0167291
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Prevents Cardiovascular Derangements Induced by Fructose Overload in Developing Rats

Abstract: The risks of chronic diseases associated with the increasing consumption of fructose-laden foods are amplified by the lack of regular physical activity and have become a serious public health issue worldwide. Moreover, childhood eating habits are strongly related to metabolic syndrome in adults. Thus, we aimed to investigate the preventive role of exercise training undertaken concurrently with a high fructose diet on cardiac function, hemodynamics, cardiovascular autonomic modulation and oxidative stress in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 55 publications
4
15
0
Order By: Relevance
“…1 d). Indeed, ET reduces insulin levels in ExFF group, thus showing the positive impact of exercise on glucose metabolism in MetS rats likewise others authors [ 19 , 20 , 41 , 42 ]. About the net glucose AUC, our results are not obvious: training seems to restore Impaired Glucose Tolerance (IGT).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…1 d). Indeed, ET reduces insulin levels in ExFF group, thus showing the positive impact of exercise on glucose metabolism in MetS rats likewise others authors [ 19 , 20 , 41 , 42 ]. About the net glucose AUC, our results are not obvious: training seems to restore Impaired Glucose Tolerance (IGT).…”
Section: Discussionsupporting
confidence: 75%
“…Consequently, as C, FF, and ExFF group are not statistically different, we propose to invalidate IGT in C group with net glucose AUC. Nonetheless, IGT is not systematically observed in fructose fed model of MetS, and this IGT would be dependent of gender [ 6 ], time of regimen [ 43 , 44 ] and is improve with training [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercised rodents treated with fructose also had a decrease in oxidative stress markers [102] and NAFLD [100], and a lower TG accumulation in liver tissue [69]. Moreover, Farah and colleagues [102] showed that aerobic exercise was able to prevent hemodynamic and autonomic cardiac dysfunction promoted by high fructose diet.…”
Section: How To Deal With the Enemymentioning
confidence: 99%
“…Indeed, elevated sugar intake has been associated with greater risks of developing cardiovascular disease [46]. However, experimental studies with high sugar added in the diet [38,47,48] or in the drinking water [49][50][51] have also shown conflicting results regarding the cardiac dysfunction due to the heterogeneity of the experimental protocol. Future investigations should be of reasonable duration, use defined animal models, and improve comparisons concerning results of relevant doses of nutrients on specific outcomes to better understand the effect of sugar consumption in the absence of potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%